Framework for evaluating risks in food supply chain: Implications in food wastage reduction - Mithun Ali, Syed; Moktadir, Md. Abdul; Kabir, Golam; Chakma, Jewel; Rumi, Md. Jalal Uddin; Islam, Md. Tawhidul (Journal of cleaner production, 2019)
Over the years, food supply chains (FSCs) have faced various challenges, including supply chain interruptions. Previous studies focused only on household food waste. In this study, the FSCs risks is connected with food wastage to develop sustainable framework to reduce food waste. A Pareto analysis is developed for risk identification based on feedback from 130 experts from food companies. Finally, a blended grey-based Decision-Making Trial and Evaluation Laboratory (DEMATEL) model has been proposed to assess the relationships among the identified major risks in FSCs. The five risks of greatest priority include: lack of skilled personnel, poor leadership, failure within the IT system, capacity, and poor customer relationship. The risk mitigation strategies for these risks are also presented. The proposed model is applied to food processing companies in Bangladesh to establish a sustainable business policy to minimize food wastage. These results can guide managers and practitioners to formulate resilient strategies to mitigate the identified risks, thereby minimizing food wastage and lead to food safety, security and sustainability across the food supply chain. The proposed model can be extended to address sustainability risk and be integrated to the internet of things for planning, monitoring, controlling, and optimizing supply chains in real time. •Key supply chain risks for food supply chains (FSCs) have been identified.•Grey-DEMATEL model is proposed to find the interactions among the key FSCs risks.•Implications of key supply chain risks on food wastage reduction are discussed.•Supply chain risks mitigation strategies are suggested.•Findings will aid managers to reduce risks and minimize food wastage in FSCs.